MICROWAVE ABSORPTION IN METASURFACES INDUCED BY EDDY CURRENTS - Hambaryan, Davit S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2024)
Efficient absorption of a metasurface composed of perpendicularly oriented graphite "meta-strips" is experimentally demonstrated, with the length of meta-strips being around half of the incident wavelength. The absorptance of the metasurface under a normally incident electromagnetic field polarized along meta-strips exceeds 90% in the spectrum of 8-12 GHz. The proposed metasurface is featured by wide incidence angle tolerance.
Keywords: microwave absorber; metamaterial; graphite metatapes